Online Journals: the Path Towards Visibility and Quality - Walker, Julie (Dhaulagiri Journal of Sociology and Anthropology, 2010)
Increasing the visibility of a journal is the key to increasing quality. The International Network for the Availability of Scientific Publications works with journal editors in the global South to publish their journals online and to increase the efficiency of the peer review process. Editors are trained in using the Open Journals System software and in online journal management and strategy so they have the tools and knowledge needed to initiate a ‘virtuous cycle' in which visibility leads to an increase in the number and quality of submissions and in turn, increased citations and impact. In order to maximise this increase in quality, it must be supported by strong editorial office processes and management. This article describes some of the issues and strategies faced by the editors INASP works with, placing a particular emphasis on Nepal Journals Online. Key words: INASP; Open Journals System; Journals Online Projects; Nepal Journals Online; journal visibility; peer review DOI: 10.3126/dsaj.v3i0.2786 Dhaulagiri Journal of Sociology and Anthropology Vol.3 2009 175-184